Respostas

2014-08-26T15:22:18-03:00
a)(x+ \frac{1}{2} ) =  (x+ \frac{1}{2} )^{2} =  x^{2} +x+ \frac{1}{4}\\b)(2x+ \frac{1}{2}) = (2x+ \frac{1}{2})^{2} = 4x^{2}+2x+ \frac{1}{4}\\c)( \frac{x}{2} + \frac{y}{2} )  = ( \frac{x}{2} + \frac{y}{2} )^{2} =  \frac{ x^{2} }{4}+ \frac{xy}{2}+ \frac{ y^{2} }{4}

Lembrando que : (a+b)^{2} =  a^{2}+2*a*b+ b^{2}   ou simplesmente : Distributiva:(a+b)^{2}=(a+b)*(a+b) =  a^{2}+a*b+a*b + b^{2} =\\  a^{2} +2ab + b^{2}

:.
2 4 2
Disponha! Não esquece de Avaliar :) :.